SOCIALIZATION OF THE IMPORTANCE OF MENTAL HEALTH FOR CHILDREN IN ORPHANAGES - Likdanawati; Irada Sinta; Rico Nur Ilham; Muammar Khaddafi; Muttaqien; Reza Juanda (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Mental health is an important aspect of a child’s development, especially for those living in foster care. These children often face significant emotional challenges due to the loss of a parent, trauma, or difficult life experiences. Socialization about the importance of mental health aims to raise awareness and provide the necessary support for children in foster care. This article discusses the importance of mental health, socialization strategies, and the roles of various parties in supporting the mental health of children in foster care, supported by current references.